Internationalisation of the Islamic thought: the contributions of Sayyed Ismail (1936-2010) - Muhsin, Sayyed Mohamed; Abdul Jalil, Mohd. Noh (Kolej Universiti Islam Melaka (KUIM), 2021)
This paper examines the intellectual contributions of Sayyed Ismail Bukhari (1936-2010), a great scholar, author and reformer from South India. Despite the profound personality and pivotal works, no serious studies are found which critically scrutinise his theses on Islamic thought and relevantization of revealed knowledge. Using the evaluative and analytical methods, this research investigates the works of Sayyed Islmail and his efforts for expanding the Islamic thought to an international audience. Based on the study, it is found that he authored majority of his books, if not all, in Arabic language for the purpose of reaching out, beyond his local community, to a huge readership from the Muslim world. Sayyed Ismail produced seminal works on Quranic exegesis, hadith, fiqh, theology and collection of Arabic Khuṭbahs on the topical issues of his time. This study also finds that Sayyed Ismail is indeed a reformer from Kerala whose works involve bringing the Muslim communities to champion the cause of humanity based on the teachings of Islam.